Exploration of coping strategies among bereaved young adults using six-part story method (6PSM) - Merikan Aren; Venessha Sambasivan (Indonesian Institute for Counseling, Education and Theraphy, 2021)
The purpose of this research was to explore the coping strategies among bereaved young adults using Six-Part Story Method (6PSM). More specifically, this study was meant to identify the strengths of coping using 6PSM and the suitability of 6PSM among young adults in counselling approach. Counselling session was adapted as a medium for data collection with the aid of 6PSM as an intervention technique. Purposive sampling and snowball sampling was used to identify the most suitable participants to contribute in this study. The ethics of research and counselling such as anonymity, confidentiality, information disclosure, and the acquisition of informed consent were followed strictly throughout this research. The data collected was then analyzed using content analysis by categorizing the data into themes that present in the BASICPh model introduced by Mooli Lahad (Belief, Affect, Social, Imagination, Cognitive, and Physical) Other than that, this study had also showed that themes such as belief, affect, and social are highly used among young adults as a way of dealing with bereavement. Not only that, this study had also found that the process of completing 6PSM enables an individual to express themselves in a way that synchronizes with the BASICPh model of coping. Based on the findings, this study would like to implicate that the coping strategies of bereaved young adults falls under the themes of belief, affect, and social. In addition, it also implicated that 6PSM is suitable to be used as an intervention in counselling young adults.